PRINCIPAL’S LEADERSHIP IN IMPLEMENTING ONLINE LEARNING DURING THE PANDEMIC: A CASE STUDY AT SMP INDONESIAN CREATIVE SCHOOL (ICS) - Corry Monesty Alfikheir; M. Nur Mustafa; Afrianto Daud (International Journal of Educational Best Practices, 2022)
This research's objective is to describe the principal's strategy for online learning and how the principal innovates to reach effectiveness in learning during the COVID-19 pandemic at SMP Indonesian Creative School (ICS) Pekanbaru. This qualitative research employs a case study design. Data were collected using semi-structured interviews, observation, and documentation techniques. The results showed that the principal of SMP ICS Pekanbaru carried out several strategies to improve effective learning during the pandemic. The strategies include setting the right curriculum, choosing online learning platforms, strengthening teacher capacity (capacity building), implementing routine monitoring, implementing learning evaluations, strengthening collaboration with parents, and strengthening student motivation. From the innovation aspect, the principal facilitates the existence of teaching stations and the Learning Management System (LMS) application in managing integrated, structured, and effective learning. Thus, we can conclude that the principal performed well in managing the school with all the limitations during the pandemic.